Investigating the Relationship between Knowledge Management Dimensions and Organizational Performance in Lean Manufacturing - Mohammad Forghani; Ali Tavasoli (International Journal of Management, Accounting and Economics, 2017)
The objective of this research is to study the relationship between knowledge management dimensions and organizational performance in lean manufacturing. In this regard, five research hypotheses were tested. Research statistical population included staffs of Mes-E- Sarcheshmeh Company. 194 individuals of research samples were selected through simple random sampling method. Research data were collected through knowledge management standard questionnaire and researcher made organizational performance questionnaire. Data were analyzed using SPSS19 software; further, Kolmogorov-Smirnov test and Pearson correlation test were also used. Research results indicated that there is a significant relationship between knowledge management dimensions and organizational performance in lean manufacturing.